2014
DOI: 10.1111/mec.12748
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drift and admixture on population structure of American black bears (Ursus americanus) in the Central Interior Highlands, USA, 50 years after translocation

Abstract: Bottlenecks, founder events, and genetic drift often result in decreased genetic diversity and increased population differentiation. These events may follow abundance declines due to natural or anthropogenic perturbations, where translocations may be an effective conservation strategy to increase population size. American black bears (Ursus americanus) were nearly extirpated from the Central Interior Highlands, USA by 1920. In an effort to restore bears, 254 individuals were translocated from Minnesota, USA, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 71 publications
2
32
1
Order By: Relevance
“…Classical population genetics theory was developed based on semelparous species and, therefore, may not be applicable to iteroparous species that have overlapping generations, such as bears (Johnson ). Our findings combined with those of Puckett et al () support this postulation for bears but also accentuate the interplay of variables in reintroductions, some of which may be beyond management control (i.e., immigration). Additionally, Palstra and Fraser (2012) posited that the incorrect application of methods to estimate genetic parameters for iteroparous species with overlapping generations has remained a problem in wildlife studies.…”
Section: Discussionsupporting
confidence: 88%
“…Classical population genetics theory was developed based on semelparous species and, therefore, may not be applicable to iteroparous species that have overlapping generations, such as bears (Johnson ). Our findings combined with those of Puckett et al () support this postulation for bears but also accentuate the interplay of variables in reintroductions, some of which may be beyond management control (i.e., immigration). Additionally, Palstra and Fraser (2012) posited that the incorrect application of methods to estimate genetic parameters for iteroparous species with overlapping generations has remained a problem in wildlife studies.…”
Section: Discussionsupporting
confidence: 88%
“…Non-random association of alleles was detected at 11% and 8% of 66 pairwise comparisons in the 2004–2005 and 2010–2012 data, respectively, after applying Bonferroni correction (α < 0.0007). Because no consistent patterns of null alleles, HWE deviation, or linkage disequilibrium were present at identical loci between the 2 datasets, we did not exclude any loci from analyses [92]. …”
Section: Resultsmentioning
confidence: 99%
“…We collected genetics data via noninvasive sampling from Florida black bears in a subpopulation that was previously identified as being isolated and presumed to be small as a result of habitat fragmentation and loss. Estimates of genetic diversity for the HGS (Table 1) remain significantly lower than estimates for large black bear populations that resided in relatively contiguous habitats (e.g., H E > 0.70; A R > 6.00 [25, 9294]), and were comparable to populations that suffered isolation-induced bottlenecks [24, 25, 49, 95, 96]. Although a sample size discrepancy existed between the 2 periods for which we estimated genetics parameters, simulations demonstrated that H E is unaffected by differing sample sizes, as is A R if estimated via rarefaction as we did [97].…”
Section: Discussionmentioning
confidence: 97%
“…For example, private alleles in the recolonized range may be (1) rare alleles that we failed to sample in the source area or that (2) we failed to sample all possible source regions, that is, the Carson Range may not be the only Sierran region to which Great Basin bears are, or recently have been, genetically connected. Finally, (3) these alleles could be the product of new mutations, although considering the presumed mutation rates of these loci (Kristensen, Faries, White, & Eggert, ; Meredith, Rodzen, Banks, & Jones, ; Puckett et al., ) we consider this latter hypothesis unlikely. Regardless, the overall lack of evidence of genetic distinction of subpopulations strongly suggests that historical populations were indeed extirpated during the mid‐20th century from the western Great Basin.…”
Section: Discussionmentioning
confidence: 97%